The influences of mathematical beliefs on mathematics anxiety among pre-service elementary school teachers in East Borneo, Indonesia - Suci Yuniarti; Mohd. Zaki Ishak; Vincent Pang (Penerbit UMS, 2019)
The study investigates the influences of mathematical beliefs on mathematics anxiety among pre-service elementary school teachers in East Borneo, Indonesia. The sample of this study is 374 pre-service elementary school teachers from the elementary school teacher education departments in public universities in East Borneo, Indonesia. The data obtained from the questionnaire used in the study are analyzed via SPSS 21.0. The regression analysis results show that there is a significant relationship between the combination of independent variables in the model and the dependent variable. The study suggests that mathematical beliefs can predict mathematics anxiety to a small extent.